Mental Health Literacy In Health Students: A Preliminary Study - Nurdin, Andi Ardiansyah; Shaluhiyah, Zahro; Widjanarko, Bagoes (Health Science UDINUS, 2024)
Mental health become a public health concern because of its rising prevalence and severe consequences. Adolescents who are attending university are the most vulnerable to mental health problems. Students, particularly in health science programs, perceive themselves as more stressed than students in other science disciplines. As a result, strategies for preventing mental disorders, beginning with an in-depth grasp of mental health literacy, can lead to improved mental health outcomes. The purpose of this study is to figure out the aspects of mental health literacy among health students. This study used a quantitative approach with a cross-sectional design. The research variables were mental health literacy and respondent characteristics. Three hundred ninety-nine samples were recruited using accidental techniques. Data analysis used descriptive and Mann-Whitney tests. The results revealed that the mental health literacy category was lower (54.4%) than the high category (45.6%). Statistical tests showed no significant difference in mental health literacy among respondent characteristics (p>0.05). This study's practical implications include improving mental health literacy through integration into learning.